More Than Pigments: The Potential of Astaxanthin and Bacterioruberin-Based Nanomedicines - Maria Jose Morilla; Kajal Ghosal; Eder Lilia Romero (MDPI AG, 2023)
Carotenoids are natural products regulated by the food sector, currently used as feed dyes and as antioxidants in dietary supplements and composing functional foods for human consumption. Of the nearly one thousand carotenoids described to date, only retinoids, derived from beta carotene, have the status of a drug and are regulated by the pharmaceutical sector. In this review, we address a novel field: the transformation of xanthophylls, particularly the highly marketed astaxanthin and the practically unknown bacterioruberin, in therapeutic agents by altering their pharmacokinetics, biodistribution, and pharmacodynamics through their formulation as nanomedicines. The antioxidant activity of xanthophylls is mediated by routes different from those of the classical oral anti-inflammatory drugs such as corticosteroids and non-steroidal anti-inflammatory drugs (NSAIDs): remarkably, xanthophylls lack therapeutic activity but also lack toxicity. Formulated as nanomedicines, xanthophylls gain therapeutic activity by mechanisms other than increased bioavailability. Loaded into ad hoc tailored nanoparticles to protect their structure throughout storage and during gastrointestinal transit or skin penetration, xanthophylls can be targeted and delivered to selected inflamed cell groups, achieving a massive intracellular concentration after endocytosis of small doses of formulation. Most first reports showing the activities of oral and topical anti-inflammatory xanthophyll-based nanomedicines against chronic diseases such as inflammatory bowel disease, psoriasis, atopic dermatitis, and dry eye disease emerged between 2020 and 2023. Here we discuss in detail their preclinical performance, mostly targeted vesicular and polymeric nanoparticles, on cellular models and in vivo. The results, although preliminary, are auspicious enough to speculate upon their potential use for oral or topical administration in the treatment of chronic inflammatory diseases.